The Influence Of Compensation And Work Motivation On Employee Loyalty (Case Study At PT Bukit Asam TBK. Tarahan Port Unit) - Helda Liana Putri; Shiwi Angelica Cindiyasari (Jurnal Ekonomi, 2024)
Human resources are essential for every company to achieve success. PT Bukit Asam Tbk., one of Indonesia's largest coal mining companies, faces challenges in managing its workforce, particularly concerning work motivation and employee loyalty. This study aims to examine the impact of compensation and work motivation on employee loyalty at PT Bukit Asam Tbk.’s Tarahan Port Unit. While high compensation is generally thought to boost loyalty, prior studies have shown mixed findings on the link between compensation, motivation, and loyalty. Based on data from interviews and questionnaires with 156 respondents, this study employs a quantitative approach using multiple linear regression to test the hypothesis that compensation and work motivation positively influence loyalty. The findings are expected to offer PT Bukit Asam Tbk. recommendations for fostering loyalty through equitable compensation policies and enhanced work motivation strategies.